2020
DOI: 10.1101/2020.07.14.187070
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic architecture of 11 abdominal organ traits derived from abdominal MRI using deep learning

Abstract: Cardiometabolic diseases are an increasing population health burden and while several well established socioeconomic, environmental, behavioural, and genetic risk factors have been identified, our understanding of their drivers and mechanisms remains incomplete. Thus, a better understanding of these factors is required for the development of more effective interventions. Magnetic resonance imaging (MRI) has been used to assess organ health in a number of studies, but large-scale population-based studies are st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
55
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(55 citation statements)
references
References 115 publications
0
55
0
Order By: Relevance
“…However, 10 other significant variants were identified as genome-wide significant (P<5x10 -8 ) in UK Biobank. Of these 10 significant variants [29], one variant showed a suggestive association with percent pancreatic fat in our MEC-APS study population (rs118005033: Beta = 0.10, P = 0.01), three . CC-BY 4.0 International license available under a (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…However, 10 other significant variants were identified as genome-wide significant (P<5x10 -8 ) in UK Biobank. Of these 10 significant variants [29], one variant showed a suggestive association with percent pancreatic fat in our MEC-APS study population (rs118005033: Beta = 0.10, P = 0.01), three . CC-BY 4.0 International license available under a (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.…”
Section: Discussionmentioning
confidence: 86%
“…In a preprint manuscript on bioRxiv, Liu and colleagues (2020) conducted GWASes of 11 MRIassessed abdominal organ and adiposity measurements , including pancreatic volume and percent fat based on 30,000 UK Biobank participants of White British ancestry [29]. Regarding the two genome-wide significant variants in our study, rs73449607 was not observed in the European American population in MEC-APS and rs79967607 was not found to be genome-wide significantly associated with pancreatic fat in the UK Biobank population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Raw MR images were obtained from the UKBB Abdominal Protocol 35 and preprocessed as previously reported 36,37 . The data were acquired on the same model, a Siemens Aera 1.5 T scanner (Syngo MR D13) (Siemens, Erlangen, Germany), across three sites (Stockport, Newcastle, Reading, UK).…”
Section: Datamentioning
confidence: 99%
“…(7,8) Interestingly, the preprint of a recent study identifies rs4240624 as the strongest genome-wide genetic determinant of liver volume whereas no association with liver fat or liver iron content was observed. (9) Overall, the mechanisms for how the PPP1R3B polymorphism contributes to liver CT attenuation or liver metabolism are unclear.…”
mentioning
confidence: 99%